Respiratory conditions: effect of housing and other factors. Issue 1 (March 1985) - McCarthy, P; Byrne, D; Harrisson, S; Keithley, J
Abstract : The public health movement has been concerned with the relation between housing and health for well over a century. Nevertheless the Black Report still identified housing as one of the major causes of ill-health and suggested, on one indicator at least, that council housing is the least healthy form of tenure. An exploratory study concerning housing and health in a north eastern local authority area is described. It was found that smoking, work experience, and age were the most important determinants of self assessed respiratory conditions. When the background factors were held constant people in areas of 'bad' housing were found to report more respiratory symptoms than those in 'good' housing areas. Respiratory conditions were affected by the age of housing, and flats were found to be worse than houses. High rise flats were worse than low or medium rise flats.